Growth behaviour of maize under different crop establishment methods and nitrogen levels - Raihan, Obaidullah; Kaur, Ramanjit; Shivay, Y.S.; Dass, Anchal; Bari, Shah Mahmood (Annals of Agricultural Research, 2018)
A field experiment was conducted during (Kharif, April-August) season of 2015 at ANASTU,Afghanistan National Agricultural Sciences and Technology University, Kandahar, to study theeffect of crop establishment methods and N levels on maize growth and productivity in semi-aridregion of Afghanistan. The experiment consists of 12 treatment combinations i.e. three cropestablishment methods; broadcast method, line sowing and ridge sowing method in main plot andfour N levels; 0, 120, 160, 200 kg N/ha in sub-plots. Maize variety CS-200 was sown using a seedrate of 25 kg/ha. Results of this study indicated that that crop establishment methods had a significanteffect on growth parameters like plant height, dry mater accumulation and crop growth rate andrelatively higher plant height (180.5 cm), dry matter accumulation (243.8 g/plant), crop growth rate(2.28 g/plant/day) were recorded in ridge planting method. In case of N levels, maximum plantheight (183.7 cm), leaf area index (3.87), dry matter accumulation (244.1 g/plant) and crop growthrate (2.5 g/plant/day) were recorded where 200 kg N/ha was applied.